Hadis Hijab Pandangan Kontemporer: Studi terhadap Pemahaman Fatima Mernissi, Quraish Shihab, dan Muhammad Syahrur - Reimia Ramadana (Jurnal Penelitian Ilmu Ushuluddin, 2022)
This study aims to discuss the hadith about hijab in a contemporary view. This research is a qualitative type through literature study using the takhrij and syarah hadith methods with a contemporary approach. The results and discussion of this research include the definition of hijab, the term hijab in history, the term hijab today, hadith editors about hijab, hijab according to hadith, and hijab in a contemporary view. This study concludes that there is no hadith that states the term hijab as Muslim clothing, and when referring to today's era the term hijab is understood as a means of covering the genitals for women, whether it is a headscarf, headscarf, or clothes. Today's hijab is also understood not only as a tool to cover the genitals but has also developed into fashion (life style).